Social Lies in Compliments Response: (Bohong Sunat dalam Lakuan Respons Pujian) (Jurnal Bahasa, 2015)
The social lie or white lie is a common language phenomenon that exists in society. In daily communication, the social lie is an indicator of humility. It has become the norm in interaction in Asia, particularly in Malaysia, in order for communication to be effective and to allow the hearer to save "face". In this study, 60 UNIMAS students of different social backgrounds were chosen as respondents. They were given a set of questionnaires containing the 12 types of compliment responses gleaned from Manes and Wolfson's (1981) three groups of compliment responses. From this, a total of 720 responses were successfully collected. The data was then analysed with Herbert's (1986, 1990) taxonomy of compliment responses. This study found that differences exist in the types of compliment responses within the different ethnic groups. The findings show that an understanding of "social lies" depends on the individual's language background. Therefore, the findings show the unique communicative responses that help to ensure successful communication.Keywords: social lies, compliments response, pragmatics